PENGGUNAAN SISTEM AKUAPONIK DENGAN JENIS TANAMAN YANG BERBEDA TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN MAS (Cyprinus Carpio) - Juli Prahesti; Rahmad Jumadi; Andi Rahmad Rahim (Jurnal Perikanan Pantura (JPP), 2019)
Common carp (Cyprinus carpio) is one type of freshwater fish that develops very rapidly as a commercial fish. The purpose of this study was to determine the best plant species in aquaponic systems in increasing optimal growth of common carp (Cyprinus carpio). This study used a completely randomized design (RAL) with 4 treatments and 3 replications. Analysis of variance (ANOVA) was used to see significant differences in treatment. Composition of treatment K (without plants), A (kale), B (lettuce), C (pakcoy). The main observation variables include absolute weight growth, absolute length, daily growth rate, survival rate and feed conversion ratio. The results of variance analysis (ANOVA) showed very significant differences in absolute length and survival variables. Absolute weight, daily growth rate and FCR in the study did not show any real differences. The highest absolute weight growth, daily growth rate, and feed conversion ratio are perlakaun K (without plants) (1,19)g, (1,59)cm and (3,48)g. The highest absolute length is treatment C (pakcoy) which is (0.97)cm. A good survival rate is B (lettuce) treatment, that is (60.00%).